PENGARUH WAKTU TRANSPORTASI SISTEM TERTUTUP TERHADAP KELANGSUNGAN HIDUP UDANG RED CHERRY (Neocaridina heteropoda) - Marhaendro Santoso; Taufik Budhi Pramono; Alifia Nurkhasanah; Joni Johanda Putra; Saprudin (Clarias : Jurnal Perikanan Air Tawar, 2022)
Red cherry ornamental shrimp have the advantage of their bright red body color and are popularly used to beautify the contents of the aquarium. Market demand for red cherry ornamental shrimp continues to increase both online and offline. The purpose of this study was to determine the effect of closed system transportation time and the best time on the survival of red cherry ornamental shrimp after transportation and maintenance for 3 days. The method used was Completely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments given were P1 1 day (24 hours), P2 2 days (48 hours), P3 3 days (72 hours), P4 4 days (96 hours), and P5 5 days (120 hours). The shrimp used are 1.8 – 2.4 cm long and weigh 0.072 – 0.24 grams. The transportation simulation given is a shock simulation every 2 hours for 15 minutes. The results obtained showed that the closed system transportation time had a significant effect on the survival of the red cherry ornamental shrimp after transportation, but did not significantly affect the survival after 3 days of rearing. The best transportation time for the survival of red cherry ornamental shrimp after transportation was 1 day (24 hours) and 2 days (48 hours) with 96% and 91.67% survival respectively